THE CUPLÉ LA VIOLETERA IN INTERNATIONAL CINEMA: FROM THE THEATRE TO THE BIG SCREEN (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2024)
The cuplé is a type of musical show that gained great popularity in early 20th-century Spain. Delving into the above, the composer José Padilla is one of the greatest exponents of cuplé in Spain. Proof of this can be seen in the more than 300 works he composed belonging to this genre, among which La Violetera (1914) stands out. Given the above, the present text aims to study the presence of the mentioned cuplé in three case studies of international feature films — City Lights (1931), Scent of a Woman (1992), and Fading Gigolo (2013) — emphasizing the analysis and functions it serves as part of their Soundtrack. The methodology used is based on the theories proposed by Lluis i Falcó (1995), Fraile Prieto (2004), and Tagg (2006). The results obtained show that Padilla´s cuplé presents specific uses and functions in each of the analyzed films that distance it from a connection to the representation of a location associated with the Spanish cultural stereotype.
Keywords: Cuplé; José Padilla; La Violetera; Internacional cinema; soundtrack